Processing and consolidation of open data on public procurement in France (2015–2023)Zenodo - Adrien Deschamps; Lucas Potin (Data in Brief)
Public procurement can be defined as the process by which public contracting authorities purchase goods, services, and works from private suppliers. To ensure transparency and prevent favoritism and corruption, public contracts adhere to strict procedures based on calls for tenders and award notices, which are publicly accessible online. This paper introduces a tabular dataset derived from the processing and consolidation of online public procurement notices. It provides a detailed overview of public contracts awarded in France between 2015 and 2023. The dataset encompasses approximately one million contractual relationships between public authorities and companies, in over 300,000 contracts, spanning all sectors and public institutions. It includes 113 variables covering contract characteristics (procedure, subject matter, award criteria, clauses, etc.), award outcomes (award price, number of bids, etc.), as well as information on contracting authorities (type, location, main activity, etc.) and awarded firms (size, legal status, main activity, age, location, etc.). This unprecedented dataset, both in accuracy and scope, provides reliable and detailed information on every advertised contract in France for nearly a decade, making it valuable for empirical research in diverse domains such as economics, geography, law, and political science.